2017
DOI: 10.21161/mjm.86016
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of marine biofouling by aquatic Actinobacteria and coral-associated marine bacteria

Abstract: Aims:Biofouling is a common biology phenomenon occuring on ship surface. This phenomenon has become serious threat in marine industries because of great economic loss. Tributyltin has been used to prevent biofouling, but it turned to cause the environmental problem. Therefore, the discovery of alternative environment-friendly compound is necessarily needed. Methodology and results: Five Actinobacteria isolates and fourteen marine bacteria isolates were tested against the biofilm formation of eight biofouling b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Another study found Streptomyces sp. and Arthrobacter mysorens extracts had broad spectrum activity against biofouling bacteria [ 33 ]. The extracts are practicable alternatives to banned toxic copper oxide and tributyltin oxide anti-fouling coatings [ 151 ].…”
Section: Medical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found Streptomyces sp. and Arthrobacter mysorens extracts had broad spectrum activity against biofouling bacteria [ 33 ]. The extracts are practicable alternatives to banned toxic copper oxide and tributyltin oxide anti-fouling coatings [ 151 ].…”
Section: Medical Applicationsmentioning
confidence: 99%
“…Marine actinomycetes associate with a variety of aquatic organisms, including invertebrates such as sponges [ 27 , 31 ], corals [ 32 , 33 ], and echinoderms [ 7 ], as well as vertebrates such as pufferfish [ 34 ]. These interactions may encourage unique chemical ecologies that might influence the evolution of secondary metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…This biofilm stimulates macrofouling larva or spore adherence and the attachment of invertebrates and algae to submerged marine surfaces, evolving into a complex biological community . For that reason, inhibiting bacterial biofilm formation is of utmost importance to prevent biofouling formation. …”
Section: Introductionmentioning
confidence: 99%
“…can get vibriosis, which causes huge economic losses in the aquaculture . This species reportedly also forms biofilms on the surface of ship hulls and marine infrastructure (Waturangi et al, 2017). Antifouling technology is used in controlling biofouling, for example, biofouling paint.…”
Section: Introductionmentioning
confidence: 99%